Strengthening the Role of the Social Development Center for Child in the Case of Sexual Crime Against Street Children - Wahyu Beny Mukti Setiyawan; Fitriya Dessi Wulandari; Widiatama Widiatama (Universitas Slamet Riyadi, 2020)
Being a civilized nation is one of the values enshrined in the Pancasila and the Preamble of the 1945 Constitution of the Republic of Indonesia. However, today the Indonesian nation can be said to be experiencing a crisis of morality. It is proven by the rise of cases of sexual crimes that occur in the community. The irony is that the victims of sexual crimes are children. The average victims of sexual crimes are street children. In fact, almost all female street children have experienced sexual harassment and rape. The state through the Ministry of Social Affairs has subsequently formed a social institution that specifically copes the problems of street children. This institution is the Social Development Center for Child (SDC). The Social Development Center for Child (SDC) has a role in handling cases of street children. As according to the Government Regulation Number 2 of 2002 concerning Procedures for the Protection of Victims and Witnesses in Serious Human Rights Violations, victims are